Anti-Lipid Peroxidation Activities of Three Selected Fruits Juices Against Cadmium Induced Liver Damage In Vitro - Eko Suhartono; June Astri Nijka; Vini Yulia Anhar; Rizki Amalia Sari; Edyson Edyson; Dona Marisa (Journal of Tropical Life Science, 2015)
Cadmium (Cd) is one of the most toxic heavy metal. Numerous tissues both in vitro and in vivo suggest that Cd induced lipid peroxidation. The presence of antioxidant can inhbit this process. This present study was designed to determine the effects of mango, papaya, and banana juices on on malondi aldehyde levels (MDA, product of cellular lipid peroxidation) during Cd exposure in vitro. Significant differences was observed between three selected fruits juices and MDA levels and also between concentration of fruits juices and MDA levels. The highest correlation was found between banana juices and MDA levels with IC50 1,12, and followed by papaya and mango juices with IC 50 1,37 and 3,87 respectively. The findings of this study suggest that the three selected fruits juices may exert its protective action against Cd-induced lipid peroxidation in liver homogenate in vitro possibly through its antioxidant mechanism.Key WordCadmium, Lipid Peroxidation, Antioxidant Activity and Fruits Juices